2013
DOI: 10.1007/s00223-013-9722-x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Vertebral Fractures Assessed by Quantitative Morphometry in Hemodialysis Patients, Strongly Associated with Vascular Calcifications

Abstract: Few studies have provided information on the prevalence of vertebral fractures (VFs) and their risk factors in hemodialysis patients. A multicenter, cross-sectional, observational study was carried out to assess the prevalence of VFs and vascular calcifications (VCs) in 387 hemodialysis patients (mean age 64.2 ± 14.1 years, 63 % males) and in a control group of 51 osteoporotic subjects. Biochemical tests included 25(OH) vitamin D, bone Gla protein (total and undercarboxylated), and total matrix Gla protein. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 38 publications
6
30
0
1
Order By: Relevance
“…This could be rather surprising considering that VFs are more common in females than in males, at least in the general population [2]. However, we already reported a higher frequency of VFs in hemodialyzed men as compared to women [28]. These results are also consistent with another published report of our group [30] on kidney transplant recipients, demonstrating a higher prevalence of VFs in men.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This could be rather surprising considering that VFs are more common in females than in males, at least in the general population [2]. However, we already reported a higher frequency of VFs in hemodialyzed men as compared to women [28]. These results are also consistent with another published report of our group [30] on kidney transplant recipients, demonstrating a higher prevalence of VFs in men.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies of our and other groups have already demonstrated that VFs are quite common in patients on maintenance HD and associated with vascular calcifications [13,28]. To our knowledge, this is the first study attempting to evaluate the association between the SDI with several factors involved in bone and vascular disease in patients with end-stage renal failure.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations